STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V SD INPRES 12/79 TORO KECAMATAN TANETE RIATTANG TIMUR KABUPATEN BONE - Nurul Atiqa Hamsir; Rosmalah; Sudirman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is a descriptive qualitative research aimed at investigating: (1) the strategies used by teachers to improve students' learning motivation in Mathematics; (2) the challenges faced by teachers in implementing learning strategies to enhance students' learning motivation in Mathematics; and (3) the solutions employed by teachers to overcome these challenges. The research subjects were the teacher and fifth-grade students of SD Inpres 12/79 Toro. Data were collected through observation, interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that: (1) the teacher improved students' learning motivation in Mathematics by providing learning motivation, applying the question-and-answer method, using contextual examples, and giving praise to students. These strategies enhanced students' participation, understanding, self-confidence, and learning motivation during the learning process. (2) The challenges encountered by the teacher included students' lack of self-confidence, fear of making mistakes, the perception that Mathematics is a difficult subject, and differences in students' learning abilities. These challenges affected students' participation and motivation in learning Mathematics. (3) To address these challenges, the teacher implemented individual guidance, varied learning methods, repeated explanations of the material, continuous encouragement, and individual approaches with additional assistance. These solutions helped students better understand the learning materials, improved their self-confidence, and enhanced their learning motivation in Mathematics.